2016
DOI: 10.1021/jacs.6b05398
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Surface Reactivity Descriptor for Transition Metal Oxides in Oxygen Evolution Reaction

Abstract: A number of important reactions such as the oxygen evolution reaction (OER) are catalyzed by transition metal oxides (TMOs), the surface reactivity of which is rather elusive. Therefore, rationally tailoring adsorption energy of intermediates on TMOs to achieve desirable catalytic performance still remains a great challenge. Here we show the identification of a general and tunable surface structure, coordinatively unsaturated metal cation (MCUS), as a good surface reactivity descriptor for TMOs in OER. Surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
331
1
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 398 publications
(353 citation statements)
references
References 46 publications
8
331
1
13
Order By: Relevance
“…[106] Both DFT simulation results and temperature programmed desorption of O 2 demonstrated that the surface reactivity of TiO 2 increases monotonically with the density of coordinatively unsaturated titanium cation (donated as Ti CUS ). This trend is further directly verified by electrochemical tests as shown in Figure 31.…”
Section: Solid-liquid Interfacial Charge Transfer In the Oxygen Evolumentioning
confidence: 96%
See 2 more Smart Citations
“…[106] Both DFT simulation results and temperature programmed desorption of O 2 demonstrated that the surface reactivity of TiO 2 increases monotonically with the density of coordinatively unsaturated titanium cation (donated as Ti CUS ). This trend is further directly verified by electrochemical tests as shown in Figure 31.…”
Section: Solid-liquid Interfacial Charge Transfer In the Oxygen Evolumentioning
confidence: 96%
“…On the other hand, experimental results usually found that the oxygen deficient TiO 2 could work stably even in harsh oxidation conditions such as OER. [106] Recently, new finding gives a better explanation by showing that the excess charge associated with O V is not constraint to the O V sites but delocalized. [108] Moreover, the slightly reduced TiO 2 surface could only be re-oxidized in air at temperatures as high as 500 °C.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…[41,42] Specifically, the features of the metal valence states (d states) and oxygen valence states (p states), which are close to the Fermi level and thus participate in the bond formation, determine the adsorption energies of metal oxides. [43] According to theoretical studies, foreign metals have two primary effects on the electronic structure: the ligand effect and the strain effect. [44][45][46][47][48] The ligand effect refers to the perturbations of the electronic structure induced by charge transfer between neighboring metals.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…Several electronic structure factors have been used as descriptors representing the OER efficiency, including features (energy, filling, and width) of the electronic states, [43,49,50] the metal-oxygen covalency, [51,52] and the number of electrons with specific symmetry (Figure 2b). [18,53] Such descriptors enable simple prediction of efficiency without rigorously calculating the four-step energies in the OER.…”
Section: Wwwadvenergymatdementioning
confidence: 99%